Time-dependent distribution of SN-38 from injectable polymeric depots in brain tumor model - Chawan Manaspon (2019)
© 2018 IOP Publishing Ltd. Distribution study of drugs in tissues is essential to provide the information on the accumulation and penetration of drugs especially anticancer drugs from the local drug delivery system. Fluorescence and histophotological images of drug-treated tissues were used to examine drug distribution and accumulation in tumors. This work investigated the distribution profiles of SN-38 in U-87MG-bearing mice received SN-38-loaded depots via intratumoral injection. Distribution profile of SN-38 was followed-up by its self-fluorescent property. Depots comprised of three main components including PLEC (poly(D,L-lactide-random-ϵ-caprolactone)-block-poly(ethylene glycol)-block-poly(D,L-lactide-random-ϵ-caprolactone)) copolymer, glycofurol, and SN-38. Depots containing 1.6 ± 0.4 mg of SN-38 were injected into the tumors (200-250 mm 3 ) and monitored up to 18 days post-injection. Tumors at each time point were sectioned and images were acquired with fluorescence microscope. Results showed that SN-38 penetrated into the tumors at the distance of 0.75 mm from the boundary of depots. Distributed SN-38 provided the necrotic area surrounding the depots. Fluorescence images were reconstructed and showed as 3D images. High level of SN-38 accumulation in tumors was found up to day 18 post-injection at 35.4 μg g -1 of tumors. This result can confirm and explain the distribution and penetration of SN-38. The information will be valuable to the design of depots administration in clinical trial.